Assessing the New Keynesian Phillips Curve in the Euro Area Using Disaggregate Data - Milda Norkute (Lund University, School of Economics and Management, Department of Economics, 2013)
There is no a priori reason to suppose that price-setting behaviour is homogeneous across sectors and countries. Aggregate data is, however, commonly used to estimate the New Keynesian Phillips curve (NKPC), which may very well yield erroneous results if price-setting behaviour is heterogeneous. In this paper we therefore estimate the hybrid NKPC for the Euro Area using a novel sectoral data set containing quarterly observations from 1999Q1 to 2012Q1. We show that a positive relationship between inflation and real marginal cost cannot be established empirically for a majority of countries and sectors. We also perform a meta-analysis by combining the results of individual significance tests in order to assess the validity of the NKPC in each country across all sectors and in each sector across all countries. We find no empirical evidence for the NKPC in the Euro Area when this meta-analysis is used. Our results therefore raise doubts about the appropriateness of the NKPC for the analysis of inflation dynamics and monetary policy in the Euro Area.
Keywords: C12; E31; 330; New Keynesian Phillips curve; Inflation; Meta-analysis